2018
DOI: 10.1038/s41418-018-0070-2
|View full text |Cite|
|
Sign up to set email alerts
|

Lactobacillus accelerates ISCs regeneration to protect the integrity of intestinal mucosa through activation of STAT3 signaling pathway induced by LPLs secretion of IL-22

Abstract: The regeneration of intestinal epithelial are maintained by continuous differentiation and proliferation of intestinal stem cells (ISCs) under physiological and pathological conditions. However, little is known about the regulatory effect of intestinal microbiota on its recovery ability to repair damaged mucosal barrier. In this study, we established intestinal organoids and lamina propria lymphocytes (LPLs) co-cultured system, plus mice experiments, to explore the protective effect of Lactobacillus reuteri D8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
198
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 268 publications
(206 citation statements)
references
References 47 publications
7
198
0
1
Order By: Relevance
“…The proliferation of the intestinal epithelium due to the presence of intestinal stem cells (ISCs) constitutes the basis for the maintenance of the intestinal mucosal barrier against pathogen invasion and intestinal inflammation. [ The intestinal microbiota is continuously in contact with the epithelium and affects niches of ISCs to influence the proliferation and differentiation of the epithelium . Moreover, Wnt signaling directly controls cell fate, such as proliferation, differentiation, and apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of the intestinal epithelium due to the presence of intestinal stem cells (ISCs) constitutes the basis for the maintenance of the intestinal mucosal barrier against pathogen invasion and intestinal inflammation. [ The intestinal microbiota is continuously in contact with the epithelium and affects niches of ISCs to influence the proliferation and differentiation of the epithelium . Moreover, Wnt signaling directly controls cell fate, such as proliferation, differentiation, and apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, neural cells induce stem cell division of gastric [68] and intestinal [69,70] organoids, while also supporting tuft cell survival [69]. Co-culture with immune cells includes: (i) intraepithelial lymphocytes that proliferate and incorporate in the organoid epithelium [71]; (ii) macrophages that enhance barrier function and maturity of enteroid monolayers and respond to infections with E. coli [72]; (iii) lamina propria lymphocytes that mediate commensal protection of the epithelium [73]; and (iv) dendritic cells that alter stem cell fate by inhibiting secretory lineage and drive absorptive lineage [74]. The anaerobic nature of the majority of the members of the intestinal microbiota complicates its co-culture in 2D organoid systems that grow under normal oxygen concentrations [5,75].…”
Section: Complementing the System For Future Applicationsmentioning
confidence: 99%
“…The anaerobic nature of the majority of the members of the intestinal microbiota complicates its co-culture in 2D organoid systems that grow under normal oxygen concentrations [5,75]. However, introduction of some oxygen-tolerant microbiota members (and their components and by-products), in organoid cultures and other intestinal models, has allowed their influence on the intestinal SCN to be studied [62,73,75].…”
Section: Complementing the System For Future Applicationsmentioning
confidence: 99%
“…Hou and co‐workers reported that IAld promotes intestinal stem cell proliferation through stimulation of IL‐22 secretion in lamina propria lymphocytes. [ 110 ] They found that colonization of Lactobacillus reuteri in mice significantly increased intestinal epithelial proliferation and Paneth cell population via upregulation of IL‐22. Previously, IL‐22 was found to induce phosphorylation of STAT3, a JAK/STAT signaling effector molecule, which results in expansion of mouse small intestine organoids.…”
Section: Gut Microbial Metabolites and Intestinal Stem Cell Activitiesmentioning
confidence: 99%